Immunoreactivity of estrogen receptor alpha in brain and ovary of the short mackerel rastrelliger brachysoma (Bleeker, 1851) - Sinlapachai Senarat (2020)
© 2019, University of Malaya. All rights reserved. The reproductive physiology concerning the gonadotropin hormone (GTH) and its downstream target estrogen receptor alpha (ERα) is not well understood in the short mackerel Rastrelliger brachysoma, an economically important marine fish in Thailand. In this study, we tested the hypothesis that the expression of both GTH and ERα in the brain and ovary of R. brachysoma was as reported in other fish species. By applying immunohistochemical techniques, we identified the distribution of ERα-immunoreactive (ir) neurons in the brain and ovary of wild female R. brachysoma during the spawning season along with the distribution of GTHs-ir cells in the ovary. The nucleus lateralis tuberis in the diencephalon had a high number of ERα-ir neurons. In the mesencephalon, dense ERα-ir neuronal fibers were mainly found in the mesencephalic cells, stratum opticum, stratum fibrosum et griseum superficiale and stratum album centrale. Both the valvula and corpus cerebelli in the metencephalon contained ERα-ir neurons in granular and Purkinje cell layers as well as the molecular layer. The ERα-ir neurons were also observed in the medulla oblongata. In the ovary, weak ERα and moderate GTHs immunoreactivities were observed in follicular cells of oocytes in early and late vitellogenic stages. This information provides baseline data required to understand not only the activity of estrogen (E2) on the brain but also the regulatory mechanism of the hypothalamo-pituitary-ovarian axis of R. brachysoma.